ANALISIS KHARAKTER SYARIF FASHA DALAM MENGUKIR KESUKSESAN PENDIDIKAN DASAR JAMBI - Melita (UNZAH Genggong, 2022)
Jambi was formed as an autonomous regional government with municipal status determined based on the Governor of Sumatra Decree No. 103/1946, on 17 May 1946 it was signed by Tengku Mohamad Hassan, and the Municipality was upgraded to become a large city of Jambi based on Law no. 9 of 1956 concerning the formation of large urban autonomous regions, because it has officially become a municipal area, Jambi City certainly needs a mayor. The government of Jambi mayor is very different from time to time, each mayor has different ways of leading and achievements. Syarif Fasha is the 11th mayor of Jambi. The pressure of life in the past has become a stepping stone for his career. Education from parents and the reality of life has shaped Syarif Fasha's character to be a good and hard-working individual. Syarif Fasha succeeded in building Jambi to be more advanced, within three years the quality of the people of Jambi city showed an increase, the 2015 Jambi city human development index (HDI) was the highest in Jambi province, namely 75.58 numbers, life expectancy reaching 72, 31. And The average length of schooling was 10.63. Keywords: , character matter, Syarif Fasha, Jambi